2015
DOI: 10.5539/gjhs.v7n4p184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptokinase on Reperfusion After Acute Myocardial Infarction and Its Complications: An Ex-Post Facto Study

Abstract: Introduction:Emergency treatment of patients with acute myocardial infarction is very important. Streptokinase in Iran is often as the only clot-busting medication is used. The purpose of using streptokinase medication is to revive the ischemic heart tissue, although has dangerous complications too. Therefore, the present study aimed to determine the effect of streptokinase on reperfusion after acute myocardial infarction and its complications, has been designed and conducted.Materials and Methods:This is an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…76.0% male with male to female ratio of 3.1:1. Similar to our study, male dominance was also observed in a study by Taheri L et al 13 , i.e. 61.67%.…”
Section: No Of Patients (%)supporting
confidence: 92%
See 3 more Smart Citations
“…76.0% male with male to female ratio of 3.1:1. Similar to our study, male dominance was also observed in a study by Taheri L et al 13 , i.e. 61.67%.…”
Section: No Of Patients (%)supporting
confidence: 92%
“…In our study, 3.33% and 5.83% patients were reported with VT/VF in SK and non SK groups (p=0.297), respectively and overall frequency of VT/VF was 4.34%. However, higher VF rate was reported in a study by Taheri L et al 13 , i.e. 8.7% and 5.3% in SK and non SK groups, respectively.…”
Section: No Of Patients (%)mentioning
confidence: 54%
See 2 more Smart Citations
“…The next level of treatment is systemic thrombolysis with streptokinase or tissue plasminogen activator (TPA); these medications can reduce mortality in LMIC. [ 24 26 27 ] Interventional approaches such as PCI with balloon angioplasty or stenting require greater infrastructure and more advanced practitioners. PCI was shown to have better outcomes than thrombolysis.…”
Section: Resultsmentioning
confidence: 99%